I RUSSIAN CONGRESS WITH FOREIGN PARTICIPANTS “EMERGENCY ENDOSCOPY”. MATERIALS OF CONFERENCE. PART 2 - T. P. Pinchuk (Неотложная медицинская помощь)
I Russian Congress with foreign participants “Emergency endoscopy”. Materials of conference. Part 2.